2021
DOI: 10.1177/14738716211012608
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of law and legal Process: An opportunity missed

Abstract: Visual representation of the law and legal process can aid in recall and discussion of complicated legal concepts, yet is a skill rarely taught in law schools. This work investigates the use of flowcharts and similar process-oriented diagrams in contemporary legal literature through a literature review and concept-based content analysis. Information visualisations (infovis) identified in the literature are classified into 11 described archetypal diagram types, and the results describe their usage quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Visualisations have been used to help investigators understand criminal patterns [13], showing timelines of activities [42] or alternative opinions [10]. Where explanatory visualisation has been used, it has been dominated by flowcharts [35], which have been used to visualise argumentation [24,43] or explain legal instructions to civil servants [45], network diagrams to visualise policy making [14,25] and schematic diagrams to explain processes in contracts [44]. This prior work led to the network metaphor being included in the design process.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Visualisations have been used to help investigators understand criminal patterns [13], showing timelines of activities [42] or alternative opinions [10]. Where explanatory visualisation has been used, it has been dominated by flowcharts [35], which have been used to visualise argumentation [24,43] or explain legal instructions to civil servants [45], network diagrams to visualise policy making [14,25] and schematic diagrams to explain processes in contracts [44]. This prior work led to the network metaphor being included in the design process.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Consequently, individuals tend to experience greater ease in assimilating information when it is presented visually, such as through diagrams, tables, videos, or audio recordings. These allow the presentation of educational materials graphically, which contributes to students' creative thinking development (Nardi, 2014;McLachlan and Webley, 2021). The possibilities of using symbols and diagrams to teach mathematics have also been studied (Presmeg, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Visualization technologies are also commonly used in law studies (McLachlan and Webley, 2021). For example, the effectiveness is characterized by the use of contract comics in law teaching, which visualizes laws.…”
Section: Introductionmentioning
confidence: 99%
“…2) have been used as visual steps to computational representation of legal argument in construction of AI (Reed et al 2007;Fenton et al 2013). However, in a recently published Fenton et al (2013) literature review it was found that in spite of calls for legal visualisations, use of diagrams to describe the inner workings of legislation or lawyerly processes remains rare (McLachlan and Webley 2020). This means that while diagrams and AI exist that exemplify a particular argument type, individual case or court judgment, there are very few exposing broader legal issues, legislation or categories of cases.…”
Section: Introductionmentioning
confidence: 99%